Studies on the formation of intermolecular interactions and structural characterization of polyvinyl alcohol/lignin film. Issue 2 (3rd March 2016) - Korbag, Issa; Mohamed Saleh, Salma
Abstract : The intermolecular interactions of lignin with a hydrophilic polymer, poly (vinyl alcohol) (PVA), were studied using Nuclear Magnetic Resonance (NMR) and FT-IR spectroscopy of PVA/lignin blend fibres prepared by casting method. The structure of polyvinyl alcohol/lignin blended film has also been studied. The FT-IR technique indicates the formation of strong intermolecular hydrogen bonds between the hydroxyl groups of PVA and lignin. 1 H and 13 C NMR spectra of the blend show extra peaks which confirm the formation of strong intermolecular hydrogen bonds between the hydroxyl groups of PVA and lignin. The results show that there is some specific intermolecular interaction between PVA and lignin.